Primary Sleeve Gastrectomy and Leaks: The Impact of Fundus-Wall Thickness and Staple Heights on Leakage—An Observational Study of 500 Patients - Boeker, Clara; Schneider, Barbara; Markov, Valentin; Mall, Julian; Reetz, Christian; Wilkens, Ludwig; Hakami, Ibrahim; Stroh, Christine; Köhler, Hinrich (Frontiers in Surgery, 2021)
Introduction: The most feared complication of laparoscopic sleeve gastrectomy (LSG) is staple-line leakage. Staple height and fundus-wall thickness might influence such leakage, and this study examined their possible impact on leak incidence. Factors including gender, age, comorbidities, and reinforcement of the staple line were also investigated. Methods: A total of 500 patients between 17 and 71 years of age who were scheduled for LSG were selected to participate in the study. For technical reasons, 53 were excluded. The fundus-wall thickness of 447 patients after LSG was investigated. The impact of staple height, fundus wall thickness, demographic and medical factors on leak incidence were investigated. Most of our patients (309) were female (69%), while 138 were male (31%). Results: The mean thickness of the proximal fundus wall was 2904µm, 3172µm in men and 2784µm in women.The leak rate was 4.9%. Age, fundus-wall thickness, and BMI showed a strong influence on leak risk, but this effect was significant only for age (p = 0.01). Patient gender and staple size showed no significant influence on the correlation between fundus-wall thickness and leak risk. Gender displayed a small effect of influence on this correlation, with η2 = 0.05. Discussion: Because older age had a significant effect on increasing the risk of staple-line leakage, there is a need for a more specific focus on these patients. Thinner fundus wall and female gender might predispose patients to staple-line leaks, but a significant value could not be reached. Therefore, staple size should remain the surgeon’s choice based on clinical experience.